Consequences of Global Climate Change on Biodiversity and Food Security: A Mini Review - Hasan M. Agha; Abdulmutalib Alabeed Alkamil; Rana Tariq Yahya; Amjad Abdulhadi Mohammed; Zaid Tahseen Ali; Muneer Mohammed Saleh Alsayadi (AUIQ Complementary Biological System)
A thriving eco-system and abundant species diversity are crucial for all forms of life on Earth. Whether or not the climate remains stable has a direct impact on biodiversity and the ecosystem services that are provided by that diversity. There is a strong correlation between biodiversity and food security, and this is influencing how the impact of biodiversity on climate change is felt. Changes in the duration of the growth season for plants, the distribution of arable lands, and the availability of high-quality water are all ways in which climate change impacts agriculture. There will be numerous positive effects on the food production system as a result of biodiversity's effect on food security. Productivity increases and improved well-being are two examples. Therefore, agricultural biodiversity has an immediate impact on economic growth and quality of life.